Hometown for an hour : poems - Rose, Jennifer, 1959- (Hollis Summers Poetry Prize., 2006)
In her second collection of poems, Jennifer Rose writes primarily of places and displacement. Using the postcard's conventions of brevity, immediacy, and, in some instances, humor, these poems are greetings from destinations as disparate as Cape Cod, Kentuckiana, and Croatia. Rich in imagery, deftly crafted, and imbued with a lightness of voice, these poems are also postmarked from poetry's more familiar provinces of love, nature, and loss.